ANALISIS DAMPAK VOLUNTARY AND FORCED COMPLIANCE TERHADAP TINGKAT KEPATUHAN PAJAK UMKM DI KOTA SEMARANG - Awaliyah, Khikmah Rizqi; Purwanti, Evi Yulia (Fakultas Ekonomika dan Bisnis, Universitas Diponegoro, 2018)
The increasing ratio and realization of MSMEs tax revenue in Semarang City is not matched with the level of tax compliance where the realization of tax revenue in Semarang City every year is always under 100% of the target set.This shows the low level of MSMEs tax compliance problem in Semarang City. This study aims to analyze the effect of tax knowledge, justice perspective, perceptions of tax evasion opportunities, and perceptions of tax sanctions on the level of tax compliance of MSMEs in Semarang City. The type of data used in this study is the primary data obtained from 101 samples of MSMEs in Semarang City as well as the secondary data obtained from several related agencies as the supporting data. Data analysis was conducted by using binary logistic regression analysis. The results of study showed that tax knowledge and perception of justice variables significantly influence MSMEs tax compliance in Semarang City. Most of the actors of MSMEs (>50% of respondents) have a high taxknowledge, especially in tax-aware indicators about the obligation to have NPWP for MSME which has a turnover of not more than 4.8 billion but have a low perception of justice where only 1 of 5 indicators that have the number of respondents >50% of indicators of perception of justice about the assumption that tax regulations are set for the benefit of all parties not only for the sake of one party, the rest of the respondents feel that the MSMEs tax is still not fair. Meanwhile, the perception variables of tax evasion opportunities and perception of tax sanctions have no significant effect to MSMEs tax compliance in Semarang City.